A General Synthetic Approach and Photophysical Properties of Regioselectively Fluorinated [5]‐ and [6]‐Helical Bispiroindenofluorenes. Issue 9 (3rd September 2020) - Caivano, Ilaria; Tošner, Zdeněk; Císařová, Ivana; Nečas, David; Kotora, Martin
Abstract: A first series of fluorinated [n]helical compounds (n=5 and 6) with the dihydroindenofluorene scaffold was prepared in 5 or 9 (octafluorinated dihydroindenofluorene) steps and their photophysical properties were determined. Rh‐catalyzed intramolecular [2+2+2] cyclotrimerization of triyndiols, which were prepared in a modular fashion from simple starting material such as fluorinated haloarylcarbaldehydes, to the intermediate [n]helical dihydroindeno[2, 1‐ c ]fluorene‐5, 8‐diols was the crucial synthetic step and proceeded with high efficacy. Their further transformation gave the desired selectively fluorinated bispirodihydroindeno[2, 1‐ c ]fluorenes. Their absorption and emission spectra were recorded. The fluorescence quantum yields were up to 92 % and the emission maxima were red‐shifted in comparison with their non‐fluorinated counterparts (386‐413 nm). Abstract : Fluorinated helical dispirodihydroindenofluorenes : Fluorinated haloarylcarbaldehydes serve as starting material for rapid 5‐step synthesis of selectively fluorinated [n]helical bispirodohydrondeno[2, 1‐ c ]fluorenes (n=5, 6). Intramolecular catalytic cyclotrimerization was used to assemble the basic molecular framework. The fluorinated dihydroindenofluorenes had emission fluorescence maxima in the range of 386–413 nm, with quantum yields up to 0.92.